Use of paracetamol for the treatment of patent ductus arteriosus in premature Newborns: A systematic review (Research, Society and Development, 2022)
Objective: Patent ductus arteriosus is associated with multiple complications and high neonatal mortality. This study aimed to evaluate the efficacy and benefits of paracetamol compared to ibuprofen and indomethacin, non-steroidal anti-inflammatory drugs usually used to close the ductus arteriosus in premature newborns. Data source: We searched the PubMed, SciELO, Lilacs, Bireme, ClinicalTrials.gov and Embase databases for articles published between January 2005 and December 2020. The descriptors used were: premature newborn, patent ductus arteriosus, pharmacotherapy, closure and paracetamol / acetaminophen. The quality of the articles was evaluated by the classification of the Oxford Centre for Evidence based Medicine. Data synthesis: The efficacy of paracetamol is comparable to that of ibuprofen and indomethacin, and it is associated with lower rates of gastrointestinal and intracerebral hemorrhage, spontaneous intestinal perforation, thrombocytopenia, hepatic and renal intolerance, and lower serum values of urea, creatinine, and bilirubin. Furthermore, it is more advantageous than placebo or nonintervention and may be the best option in cases with contraindications for other drugs. Gestational age and birth weight were factors that influenced the efficacy of paracetamol and showed reduced efficacy in extremely premature newborns with extremely low and very low birth weights. Conclusions: Other clinical and prospective studies are needed to support the indication of paracetamol in patent ductus arteriosus. However, this drug proves to be a promising pharmacological alternative, having similar efficacy to classic non-steroidal anti-inflammatory drugs, with fewer adverse effects.